Intraoperative hepatic subcapsular spider-like telangiectasia sign for the definitive diagnosis of biliary atresia - Kaizhi Zhang; Yan Tang; Rui Liu; Zebing Zheng; Chengyan Tang; Yuanmei Liu; Zhu Jin (BMC, 2023)
Abstract Objective To evaluate the accuracy of intraoperative hepatic subcapsular spider-like telangiectasia (HSST) sign for differentiating biliary atresia (BA) from other causes of hepatic cholestasis. Methods The data of 69 patients with jaundice treated from January 2019 to December 2021 were retrospectively analyzed. Based on intraoperative cholangiography (IOC), the patients were divided into two groups: the BA group (n = 49) and the non-BA group (n = 20). The biochemistry tests, liver ultrasound, liver stiffness value and HSST sign of the two groups were compared. Results The incidence of abnormal gallbladder, elevated γ-glutamyl transpeptidase (γ-GGT) > 182.0U/L and abnormal liver stiffness (> 6.4 kPa) in BA group were significantly higher than those in non-BA group (P < 0.001). The HSST sign was present in all BA patients and not found in non-BA group. The area under receiver operating curve of direct bilirubin(DBIL), γ-GGT, abnormal gallbladder, liver stiffness value and HSST sign were 0.53, 0.84, 0.78, 0.96, and 1.00, respectively. The sensitivity, specificity, positive predictive value (PPV) and negative predictive value(NPV) of HSST sign in the diagnosis of BA were all 100%. Conclusion Presence of HSST sign on diagnostic laparoscopy is highly suggestive of BA.It can be used in the differential diagnosis of BA and non-BA. Level of evidence Level III.